PENGGUNAAN TEKNIK PSIKODRAMA UNTUK MENINGKATKAN KONSEP DIRI SISWA - Nurfaizal, Nurfaizal (JURNAL FOKUS KONSELING, 2016)
This study based on the problem experienced by 20 students of Senior High School PGRIPagelaran who have negative self concept. In order to enhace studentsâ self concept, theresearcher tries to use pychodrama technique for investigating group guidance service. Itis a solution to improve studentsâ self concept. This study employs pre-experimental Pre-test post-test One Group Design. This study was conducted at the X class of Senior HighSchool PGRI Pagelaran in accademic year 2013/2014. The research subject are 20students. Hypothesis testing was applied by comparing the average score of pre-test andpost-test, and the T test was consulted with value of T Table at significant level 1% andd.b.= N-1=20-1=19. The result shows that the use of psychodrama technique canimprove self concept. The result was proven by significant change of average score pre-test and post test which treated psychodrama technique is 67.5 change into 89.85 or t (o)= 8,196 > t (t) = 2,861, therefore Ho rejected and Ha accepted.Keywords: psychodrama, self concept.